Antibiotic Susceptibility of Staphylococcus aureus from Artisanal Cheeses Sold in Markets of Jaén - Vásquez Requejo, Jarly Jhonmy (2025)
The consumption of artisanal cheeses is high in Jaén, but the hygienic and sanitary conditions during their sale and consumption are often inadequate, increasing the risk of exposure to Staphylococcus aureus (S. aureus). This study aimed to examine the prevalence and antibiotic resistance profile of S. aureus strains isolated from artisanal cheeses distributed in Jaén markets in 2024. A total of 100 samples, each weighing 25 grams, were collected from the 25 stalls available across five local markets. The techniques used for isolating and identifying S. aureus included mannitol salt agar, Gram staining, and catalase and coagulase tests. Antibiotic resistance was assessed using the Kirby-Bauer disk diffusion method, following INS guidelines, with sensitivity disks for amoxicillin, tetracycline, ciprofloxacin, levofloxacin, and norfloxacin. Of the 55 strains identified as S. aureus, 52.7% showed resistance to amoxicillin. For fluoroquinolones (ciprofloxacin, levofloxacin, and norfloxacin), sensitivity of 96.3%, 96.3%, and 90.9% were observed, respectively. Additionally, 61.8% of strains were sensitive to tetracycline. In conclusion, the samples demonstrated resistance to amoxicillin but considerable sensitivity to tetracycline and fluoroquinolones.